Equal Incremental Fuel Cost Approach for Multi Area Operation of Power System - V, Sudhakar A V; Chandram, Karri; A, Jaya Laxmi; V, Sudhakar A V; Chandram, Karri; A, Jaya Laxmi (Iraqi Journal for Electrical and Electronic Engineering, 2017)
This paper presents a novel approach, Equal Incremental fuel cost (λ-Concept) approach, for solving Multi Area Economic Dispatch (MAED) problem. It is a simple approach and developed from the basic observation of incremental fuel cost of an area. The proposed approach has been tested on 4-area system with four generators in each area and a large 2-area system consists of 120 generators. The suggested algorithm has been tested extensively by considering the different tie line power transfer limits and useful recommendations are provided. Further, the impact of tie line power transfer limits on total fuel cost is also discussed. It is found from the test cases that the proposed method is shown to be robust, very fast and extensible to include a large class of problems. The simulation results of the proposed method have been compared with the existing methods.